Toxicity Test of Zinc on Contaminated Soil by Petroleum Products (Fuel Oil) around Pertamina Rewulu-Cilacap Pipeline Bantul, Yogyakarta by Using Mung Bean (Vigna radiata) and Water Spinach (Ipomoea aquatica) - Latumahina, Linda Johana; Tanzil, Yosua; Suyanta, Suyanta; Suherman, Suherman (Indonesian Journal of Chemistry, 2024)
Toxicity test of zinc on contaminated soil by petroleum products around the Pertamina Rewulu-Cilacap pipeline, Bantul, Yogyakarta by using mung bean (Vigna radiata) and water spinach (Ipomoea aquatica) have been studied. This study aims to investigate the physico-chemical properties, adsorption, and desorption of soil samples, and the effect of Zn toxicity on the growth of mung bean and water spinach. The physico-chemical properties were evaluated including moisture content, ash content, pH, conductivity, total organic carbon, cation exchange capacity, and heavy metal content. In addition, total petroleum hydrocarbon was analyzed by using GC-MS, and samples were characterized by using FTIR and XRD. The adsorption and desorption capacities of Zn were determined by an atomic absorption spectrophotometer (AAS) measurement. Toxicity test was conducted on the growth of mung bean and water spinach. This study showed that soil sample point III had the highest Zn content at 632.26 mg kg−1. Adsorption isotherms of zinc metal followed the Langmuir isotherm model and maximum adsorption occurred at 100 mg kg−1. Optimum desorption takes place at the concentration of citrate acid 0.7 mol L−1 and at pH 3. Toxicity test results revealed that zinc metal at high concentrations was found to be toxic to seedling growth.